Intervensi Gizi dalam Penanganan dan Pencegahan Stunting di Asia: Tinjauan Sistematis - joko tri atmojo; Rina Tri Handayani; Aquartuti Tri Darmayanti; Catur Setyorini; Aris Widiyanto ((JKG) Jurnal Keperawatan Global, 2020)
Background: Stunting has dire consequences for children's health in the short term which can decrease cognitive, motor and verbal abilities, increase morbidity and even mortality. Nutrition intervention is absolutely necessary in efforts to reduce and prevent stunting. Purpose this study is to identify nutrition interventions in handling and preventing stunting in Asia. Methods: This search was conducted from September to October 2019, through various databases including PubMed, EMBASE, and CINAHL. Article inclusion criteria: randomized controlled trial, retrospective, observational study, case study, review, systematc review, and meta-analysis. Results: The review results show that in Asia there were 8 specific nutrition programs and 9 sensitive nutrition programs. Conclusion: Interventions for sensitive and specific nutrition programs have been shown to reduce the incidence of stunting and address the long-term effects of stunting in various countries in Asia, but the programming and implementation can be arranged according to country needs and conditions.